„Mir schwätze Saarlännisch“. An overview of the special features of the Rhine and Moselle Franconian dialects in Saarland - Besse, Nathalie (Revista de Filología Alemana, 2024)
The Saarland, the smallest territorial state in the Federal Republic of Germany, is rarely at the centre of dialectological studies, although it has a very diverse dialect landscape to offer. This research desideratum is addressed in the present study, which is based on a corpus of 25 language recordings from the three dialect areas found in the Saarland (Rhine Franconian, transitional area, Moselle Franconian). A questionnaire with a selection of Wenker sentences served as the basis for the recordings, which were collected specifically for this study. The material is analysed with regard to linguistic features on four levels: phonetic-phonological, morphological, lexical and syntactic, with the focus on the first level, which is dealt with in more detail. The aim of the study is to provide an overview of how the various dialects are spoken in different areas of the Saarland and what similarities, differences and special features can be identified.
Keywords: Saarland; dialectology; Rhine Franconian; Moselle Franconian; language recordings; Wenker sentences